Arabic Expresion Teaching Model on Youtube “Muhaiban Channel” - Firman Nurul Fauzi; Sonia Mu'tasimatul 'Azimah; Nurul Syahrayni; Danial Hilmi (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Purpose - The objectives of this study are: (1) to describe the learning model of Arabic expressions in Muhaiban Channel (2) to find out the content of Arabic expressions in Muhaiban Channel Design/methodology/approach - This research used a descriptive qualitative method with the type of literacy study. The method used to collect research data is in the form of books about teaching Arabic, teaching vocabulary, and selected learning media, presented and analyzed, and processed to be concise and systematic and data analysis using content analysis. Findings/result - The results of this study are: (1) the learning model starts with orientation, presentation, guided training, independent training, and closing, (2) the content of Arabic expression material starts from simple material, namely from everyday expressions which are explained in detail. Originality/value, Utilization of YouTube as a medium for learning Arabic expressions in the era of technological development Paper type, Research paper